Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XXI): The identities of D. breviscaposum and D. filibracteolum from northwestern Yunnan - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2019)
Based on examination of herbarium specimens (including type material), we demonstrate that Delphinium breviscaposum and D. filibracteolum (Ranunculaceae), both described recently from northwestern Yunnan in China, are conspecific with D. ceratophorum and D. bulleyanum, respectively, two species very common in northwestern Yunnan. We therefore synonymize D. breviscaposum and D. filibracteolum herein. Second step lectotypifications are proposed for both D. bulleyanum and D. ceratophorum.